(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Blockchain technology represents a distributed ledger that maintains a record of all transactions carried out over a network and distributes those details among the nodes involved. Bitcoin is a well-known digital money that is applied using the technology of blockchain. Instead of using the help of a local server, a cloud system uses a network of far-flung servers to store, manage, and analyze data. However, it still faces many challenges including data security, data management, compliance, and reliability. Throughout this paper, we’ve discussed some of the cloud’s most pressing issues and proposed solutions based on blockchain technology integration. In this article, we describe a brief assessment of earlier studies that discussed the integration of blockchain and the cloud. During the study, we also developed a framework to integrate blockchain with the cloud and to demonstrate the communication between the two.